Humic acid may retard damages of cells in strawberry apices in high saline environment - Lin, Yong-Hong; Chang, Yao-Tsung (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ), 2020)
Most studies were focused on the salt-resistance physiology by humic acid (HA) for strawberry in the past. For advancely verifying the remission of salt injury by humic acid, this study was conducted to evaluate K+/Na+ in the strawberry and observe cell morphology of strawberry after treatment of salt concentrations (0 and 50 mg kg-1) and HA (0, 150 and 300 mg kg-1). The results showed that the treatments of humic acid will increase the absorption of K+ (potassium ion) and reduce Na+ (sodium ion), and hence increase K+/Na+ in the root and leaf of strawberry. By the observing of SEM (scanning electron microscopy) and TEM (transmission electron microscopy), under no salt treatments, no matter the additive concentration of humic acid, the root apices of strawberries were normal and integrity. However, in the treatments of high salt concentration, the shrinking and cracking of cells in root apices of strawberries were serious and gradually getting integrity and normal after adding humic acids from 150 to 300 mg kg-1. These results showed that the appropriate treating concentration of humic acid will inhibit the salt injury on root apices of strawberries.